PENDAMPINGAN DAN PEMBERDAYAAN KADER POSYANDU DALAM PEMANTAUAN PERTUMBUHAN DAN DETEKSI DINI STUNTING PADA ANAK DI KELURAHAN LOA BAHU KECAMATAN SUNGAI KUNJANG - Ida Ayu Kade Sri Widiastuti (Jurnal Pengabdiaan Masyarakat Kasih (JPMK), 2024)
Stunting is a condition of failure to grow due to chronic lack of nutritional intake. Apart from the growth problems of children whose height is shorter than children their age, stunting also results in hampered children's cognitive and psychomotor abilities and makes children susceptible to degenerative diseases. In efforts to reduce the prevalence of stunting, the role of Integrated Healthcare Center cadres or cadres of posyandu is very important in preventing stunting and nutritional problems that can occur in children. Integrated Healthcare Center cadres are the leading component of counselling, coaching and monitoring the growth and development of children under five. Integrated Healthcare Center cadres must have knowledge and skills in carrying out early detection of stunting and screening children's growth and development. Community service aims to improve the abilities and skills of Integrated Healthcare Center cadres in carrying out early detection of stunting and screening children's growth as well as providing simple interpretations of the screening results. Implementation of activities by providing education, training in growth monitoring and stunting detection as well as integrated evaluation monitoring at each Integrated Healthcare Center /Posyandu.